Efficient Chemical Coagulation-Electrocoagulation-Membrane Filtration Integrated Systems for Baker's Yeast Wastewater Treatment: Experimental and Economic Evaluation - Hossein Nouri Alavijeh; Morteza Sadeghi; Mohammad Reza Khavari Kashani; Ahmad Moheb (Cleaner Chemical Engineering, 2022)
The present study provides technical and economic comparisons of electrocoagulation (EC), chemical coagulation (CC), integrated EC-CC, and combinations of these techniques with ultrafiltration (UF) and nanofiltration (NF) systems based on baker's yeast wastewater treatment. Key parameters such as initial pH, coagulant dosage, and stirring speed were optimized for both EC and CC methods to achieve higher removal efficiencies at lower operating costs. Evaluating EC and CC indicates EC obtained better performance by removing 77.64% and 97.49% of COD and turbidity, respectively, but higher operating costs for treating baker's yeast wastewater. CC with operating costs of 0.737$/m3 and 1.427 $/m3 using lime and polyaluminum chloride (PACl), respectively, is more cost-effective than EC with total operating costs of 3.526 $/m3. This study was the first to compare the capital costs of EC and CC, and it was revealed that CC still required less investment than EC. The combination of EC and CC methods was studied for the first time on baker's yeast wastewater. The results showed that combining CC and EC improves COD removal efficiency by 11.2% and 16.1% when compared to single EC and single CC processes, respectively. Two types of hollow fiber membranes made of polypropylene (PP) and polyvinylidene fluoride (PVDF) for the UF process and a polyamide spiral membrane for the NF system were employed in membrane filtration integrated systems. The combination of the EC-CC system with the UF and NF systems resulted in the highest COD removal efficiency, which was around 99.7% for the EC-CC(PACl)-PVDF-NF system.